A review of the genus Nothris Hübner, 1825, with description of new species (Lepidoptera: Gelechiidae) - Karsholt, Ole; Šumpich, Jan (Zootaxa, 2015)
The West Palaearctic genus Nothris is reviewed. Eight species are distinguished, and adults and genitalia are described and figured. Two species are described as new for science: Nothris gregerseni sp. n. and N. skyvai sp. n. New synonymies are established: Nothris discretella Rebel, 1889 syn. n. and N. verbascella clarella Amsel, 1935 stat. n. are considered synonyms of N. verbascella ([Denis & Schiffermüller], 1775); and N. magna Nel & Peslier, 2007 syn. n. is synonymized with N. sulcella Staudinger, 1879. Most Nothris species occur in Turkey.